2009
DOI: 10.1039/b904650j
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of negative differential resistance electrochemical oscillators: theory and experiments

Abstract: An approximate formula for the frequency of oscillations is theoretically derived for skeleton models for electrochemical systems exhibiting negative differential resistance (NDR) under conditions close to supercritical Hopf bifurcation points. The theoretically predicted omega infinity (k/R)1/2 relationship (where R is the series resistance of the cell and k is the rate constant of the charge transfer process) was confirmed in experiments with copper and nickel electrodissolution. The experimentally observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…The reaction of those molecules can thus be thought as one of the simplest yet very interesting experimental systems. Of late, Kiss and co-workers [21][22], [23], [24] have discussed the role of temperature and some electrical properties on the oscillation features. For a NDR oscillator, which typically oscillates under potentiostatic control, the authors found theoretically and experimentally that the frequency of oscillations is directly related to the square root of the velocity of charge transfer [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction of those molecules can thus be thought as one of the simplest yet very interesting experimental systems. Of late, Kiss and co-workers [21][22], [23], [24] have discussed the role of temperature and some electrical properties on the oscillation features. For a NDR oscillator, which typically oscillates under potentiostatic control, the authors found theoretically and experimentally that the frequency of oscillations is directly related to the square root of the velocity of charge transfer [21].…”
Section: Introductionmentioning
confidence: 99%
“…Of late, Kiss and co-workers [21][22], [23], [24] have discussed the role of temperature and some electrical properties on the oscillation features. For a NDR oscillator, which typically oscillates under potentiostatic control, the authors found theoretically and experimentally that the frequency of oscillations is directly related to the square root of the velocity of charge transfer [21]. On the other hand however, for HN-NDR oscillators in which the full activity of the catalyst is inhibited by a poisoning process it was found that the frequency was directly proportional to the square root of the velocity of poisoning [22].…”
Section: Introductionmentioning
confidence: 99%
“…[1] In such configurations the effects of physical parameters (series resistance, rotation rate and size of the working electrode) on oscillation properties can be quantitatively described with nonlinear analysis of predictive skeleton models for NDR type of electrochemical systems. [5-8] For example, it was shown that appearance of oscillatory instabilities with large rotation rates [7, 9-11] and large electrode sizes [7, 12] can be quantitatively contributed to the presence of a minimal ohmic (IR) drop requirement[7, 13] : large electrodes with ohmic drops that surpassed the critical IR drop exhibited oscillations while small electrodes with small IR drops retained their stable stationary states. (Note that there could also exist a maximum IR drop above which oscillations cease to exist[2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [19] examined the synchronization of bursting through the introduction of finite delays. Kiss et al [20] studied the bursting oscillations in electrochemical systems caused by changes in the geometrical structure. Li et al [21] examined the mechanism of bursting oscillations in a nonsmooth generalized Chua's circuit with two time scales.…”
Section: Introductionmentioning
confidence: 99%